The third industrial revolution in global business - Dosi, Giovanni 1953-; Galambos, Louis (Comparative perspectives in business history, 2013)
The essays in this volume probe the impact the digital revolution has had, or sometimes failed to have, on global business. Has digital technology, the authors ask, led to structural changes and greater efficiency and innovation? While most of the essays support the idea that the information age has increased productivity in global business, the evidence of a 'revolution' in the ways industries are organized is somewhat more blurred, with both significant discontinuities and features which persist from the 'second' industrial revolution